Nghiên cứu phân lập, nhận dạng Cleistantoxin từ quả cây Chà Chôi (Cleistanthus Tonkinensis Jabl., Euphorbiaceae) làm nguyên liệu thiết lập chất chuẩn / Nguyễn Lâm Hồng, Đào Tú Anh, Lê Công Vinh, Phạm Văn Cường, Đoàn Thị Mai Hương, Trần Việt Hùng - Nguyễn, Lâm Hồng
On continuance of the previous programmed screening to reveal that ethyl acetate extracts from the fruits of the 2 Cleistanthus species (C. indochinensis Merr. ex Croiz and C. tonkinensis Jabl., Euphorbiaceae) possessing a strong cytotoxicity against KB cells (88.4 and 95.2 % inhibition at 1 μg/mL), cleistantoxin and some aryltetralin lignans were isolated from these species. The obtained cleistantoxin was identified physically by appearance, melting range (199-202oC), specific rotation ([a]D20 = -133,400), and spectrometrically by 1D-NMR, 2D-NMR, HR-MS, CD, IR, UV, etc. As the major active component of the plant, Cleistantoxin proved to have a significant cytotoxicity against the following cancer cell lines: MCF-7 (IC50 = 0.036 μM), MCF-7R (IC50 = 0.014 μM) and HT29 (IC50 = 0.035 μM). In addition, cleistantoxin showed structural similarity to etoposide which is currently used for lung cancer treatment. To establish a primary chemical reference substance (PCRS), 4.023 g cleistantoxin was purified (> 99.0 % by HPLC/DAD analysis), meeting the quality and purity requirments of the International Pharmacopoeia (IP) and World Health Organization (WHO) guide.